Hybrid Profile Matching and Forest Fire Model Strategies in Serious Game Supply Chain Management Agribusiness - Saiful Bukhori; Wiji Utami; Slamin Slamin (International Journal of Supply Chain Management, 2016)
Supply Chain Management (SCM) is increasingly being recognized as the integration of key business processes across the supply chain. Any company that joined in SCM must consider the strategies of the firms competitors. This research was discuss strategy in SCM agribusiness using hybrid profile matching and forest fire model and modelled in the form of serious games. Each cigarette factories compete to get tobacco from farmers in accordance with the required quality, so farmers can compete to sell tobacco in accordance with its quality. The results of the simulations revealed that supply of tobacco from farmers to the cigarette factory is distributed in stage.